2016
DOI: 10.1111/joim.12505
|View full text |Cite
|
Sign up to set email alerts
|

High plasma osteocalcin is associated with low blood haemoglobin in elderly men: the MrOS Sweden Study

Abstract: These data add further support to the evidence indicating that the bone-specific protein osteocalcin has several endocrine functions targeting the pancreas, testes, adipocytes, brain. An additional novel finding is that osteocalcin may also have a paracrine function as a regulator of haematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Thus, hgb may affect bone mass in a way not captured by DXA. The association between hgb and osteocalcin has previously been reported by our group [37]. Adjusting for CRP did not change our results substantially.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, hgb may affect bone mass in a way not captured by DXA. The association between hgb and osteocalcin has previously been reported by our group [37]. Adjusting for CRP did not change our results substantially.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, a correlation study in healthy older adults showed that plasma osteocalcin levels were positively associated with global cognitive performance in healthy women (Bradburn et al 2016). Interestingly, a recent, relatively extensive study showed an association between high blood osteocalcin levels and low serum hemoglobin in elderly men (Lewerin et al 2016). New knowledge of the interactions between bone and extraskeletal systems may signify a new approach, not only in the treatment of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…No adjustments were made for osteocalcin or estradiol in those studies (102)(103)(104). We have previously shown that in elderly men estradiol is positively and osteocalcin negatively correlated with Hb (171,172). Additionally, in the Italian and German studies, DXA was not used for assessing bone density but rather peripheral quantitative computerized tomography (pQCT) and ultrasound, respectively (102)(103)(104).…”
Section: Hemoglobin Neutrophil-and Platelet Countmentioning
confidence: 99%